The Mediating Role of A Learning Organization On The Relationship Between Total Quality Management and Operational Performance - Wiraditya Gusti Pratama; Dessy Isfianadewi (Journal Research of Social Science, Economics, and Management, 2023)
This research was carried in order to have a deeper comprehension of the role that learning organizations play in mediating the relationship that exists between Total Quality Management and operational performance. This research was carried out at leather SMEs in the Garut Regency. In this study, quantitative research methods are used, and a questionnaire is used to collect the data. The individuals responsible for Leather SMEs in Garut Regency make up the population that was used for this study, and there were a total of 106 responses. The data from this study are analyzed using descriptive analysis and SEM analysis. The analysis is done with the help of the SmartPLS program. The findings of this study show that Total Quality Management has a significant and positive effect on learning organizations. The learning organization then has a significant and positive impact on the operational performance of the business. And learning organization has a significant and positive influence on the mediation of the relationship between Total Quality Management and operational performance.